Case Report: Application Of Walking Activity Intervention To Reduce Pain Scale And Blood Pressure In Clients With Hypertension In Tangerang Regency - Rohilah, Rohilah; Winahyu, Karina Megasari (Nursing Case Insight Journal, 2024)
Hypertension, a condition in which the blood pressure exceeds normal limit, can lead to severe complications, such as heart disease, stroke, and kidney disease. The aim of study is to describe family nursing care for Mrs. S, a Hypertension patient, with walking activity intervention against reduction of pain scale and blood pressure. The method used is a case report with descriptive technique. Based on the assessment, data was obtained that the patient had a history of hypertension twelve years ago and complained of dizziness, pain in the nape, often consuming salty food, rarely exercising, and not having a routine health check. Nursing diagnosis in patients is ineffective health management, the intervention is to monitor blood pressure on the pain scale and provide nonpharmacological techniques to lower blood pressure and pain scale by the application of walking activities. The implementation of nursing carried out is walking activities for 30 minutes on three consecutive days within a week. The results of the nursing evaluation problem were resolved. Conclusion from the application of walking activities given to clients to lower blood pressure and pain scale.